Communication through Go’et as an Off-Record Politeness Strategy in Health Promotion: A Sociopragmatic Study - David Djerubu; Gabriel Fredi Daar (Celt: A Journal of Culture, English Language Teaching and Literature, 2026)
Health promotion is a key factor in encouraging behavioral changes toward healthier living, particularly in communities with strong cultural traditions like Manggarai, Flores Indonesia. Traditional communication approaches such as Go’et, an indirect politeness strategy (off-record politeness), are crucial in delivering sensitive messages without offending. This study aims to; 1) Identify the types of Go’et in the Manggarai language that can be utilized in health promotion contexts. 2) Explore how Go’et is employed as an off-record politeness strategy in health promotion in Manggarai. The research employs a qualitative approach with ethnographic methods to gain an in-depth understanding of the practice of Go’et communication in health promotion within the Manggarai community. The study was conducted in Pateng and Rego, Manggarai Barat Regency, Flores Indonesia, with 10 participants, including traditional elders, community leaders, and health workers involved in health promotion. Data were analyzed using thematic analysis, which involved data coding, theme identification, and in-depth interpretation. Triangulation was applied by comparing data from interviews, observations, and documents to ensure the validity of the findings. The study revealed that go’et has the potential to be integrated into health promotion strategies. Several types of Go'et can be employed in health promotion. As an Off-Record Politeness strategy, there are some characteristics of Go’et, that make it potentially applied in health promotion; its use of indirectness, Go’et helps save interlocutor’s face for sensitive health topics, and Go’et provides space for building trust and cultural resonance. The study also found that Go’et typically conveys advisory messages and hopes for the health of the community. Despite its unique characteristics, some challenges need to be addressed by healthcare workers when dealing with Go’et in terms of promoting health. The study contributes to the theory of linguistic politeness, particularly regarding off-record politeness strategies, and highlights their application in health promotion within the indigenous Manggarai community.